Ambulatory Blood Pressure Monitoring to Assess the White‐Coat Effect in an Elderly East African Population. Issue 5 (18th February 2015) - Ivy, Ashleigh; Tam, Jonathan; Dewhurst, Matthew J.; Gray, William K.; Chaote, Paul; Rogathi, Jane; Dewhurst, Felicity; Walker, Richard W.
Abstract : The authors hypothesized that published hypertension rates in Tanzania were influenced by the physiological response of individuals to blood pressure (BP) testing, known as the white‐coat effect (WCE). To test this, a representative sample of 79 participants from a baseline cohort of 2322 people aged 70 years and older were followed to assess BP using conventional BP measurement (CBPM) and ambulatory BP monitoring (ABPM). There was a significant difference between daytime ABPM and CBPM for both systolic BP (mean difference 29.7 mm Hg) and diastolic BP (mean difference 7.4 mm Hg). Rates of hypertension were significantly lower when measured by 24‐hour ABPM (55.7%) than by CBPM (78.4%). The WCE was observed in 54 participants (68.4%). The WCE was responsible for an increase in recorded BP. Accurate identification of individuals in need of antihypertensive medication is important if resources are to be used efficiently, especially in resource‐poor settings.